Colorimetric determination of copper in fertilizers - Alcarde, J. C.; Catani, R. A.; Ponchio, C. O. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1971)
This paper deals on the adaptation of the diethildithiocarbamate colorimetric method in the determination of copper in fertilizers. Were studied the influence of high phosphate concentrations, preparation techniques of extracts of mineral fertilizers and fertilizers containing organic materials and precision and accuray of the method comparatively with the iodometric method. The results allowed to conclude that the diethildithiocarbamate colorimetric method is not influenced by amounts of phosphate up to 4 mg. Its precision and accuray for copper determination in fertilizers is comparable to the iodometric method.